Criminal Responsibility for Concealing Truth in Finance (Journal of Legal Studies, 2019)
The disguise of truth as one of the main sources of blameworthy in the Qur'an and the customs has been extremely condemned and has cautioned the concealer. In light of the Quranic documentation and the legitimacy of the disguise of reality, it has been acknowledged and acknowledged that instances of household and outside business sectors that reason doubt of merchants and uncertainty in the monetary space have been a wellspring of perplexity by the gatherings to the agreement. In Iran's law, regardless of the expectation of common risk, including pay and end for hiding reality, no assurance of criminal requirement has been predicted. In this article, alluding to the refrains and portrayals, the standard of wellbeing and the guideline of the supply of products reality in contracts where the purposeful camouflage causes unsalvageable harm, by adjusting the components of wrongdoing, notwithstanding thoughtful risk, for hiding criminal obligation.